Vice patrol: cops, courts, and the struggle over urban gay life before Stonewall - Lvovsky, Anna (The University of Chicago Press, 2021)
Intro -- Contents -- List of Illustrations -- Introduction -- One. When Anyone Can Tell -- Two. Expert Witnesses on Trial -- Three. Plainclothes Decoys and the Limits of Criminal Justice -- Four. The Rise of Ethnographic Policing -- Five. Peepholes and Perverts -- Six. The Popular Press and the Gay World -- Epilogue -- Acknowledgments -- List of Abbreviations -- Notes -- Index.